Implementasi Pnpm Mandiri Dalam Peningkatan Kesejahteraan Masyarakat - Chalid Sahuri; Sofia Achnes; Dadang Mashur; Zulkarnaini ' (Jurnal Kebijakan Publik, 2012)
Thepurpose of this study is to analyze and explain the mechanism of the implementation of the PNPMMandiri in Sub Base Sub Base East Kerinci Kerinci Pelalawan. The research relies on interviewswith informants between researchers deliberately researchers determine in accordance with theneeds of the required information. Later observations for viewing and analyzing events in thefield. The results indicate the implementation of poverty reduction through PNPM Mandiri in SubBase East Kerinci less successful overall. This happens because of a lack of capability in managingand implementing activities posted coached the poor through its resources.